Triphenylamine-embedded copper(ii) complex as a "turn-on" fluorescent probe for the detection of nitric oxide in living animals. Issue 44 (31st October 2022) - Shang, Zhuye; Shu, Li; Liu, Jianhua; Meng, Qingtao; Wang, Yue; Sun, Jianguo; Zhang, Run; Zhang, Zhiqiang
Abstract : A triphenylamine-copper(ii )-based fluorescence probe (NZ -Cu 2+ ) has been developed for the detection of NO in vivo . Abstract : Nitric oxide (NO) is one of three major signaling molecules, which is involved in a large amount of physiological and pathological processes in biological systems. Furthermore, more and more evidence indicates that NO levels are closely associated with several aspects of human health. Accordingly, it is of great significance to develop a convenient and reliable detection method for NO in biological systems. In this work, a novel triphenylamine-embedded copper(ii ) complex (NZ -Cu 2+ ) has been developed to be used as a fluorescence probe for the detection of NO in living animals. The proposed sensing mechanism of NZ -Cu 2+ towards NO has been confirmed by high-resolution mass spectrometry, spectroscopic titration and density functional theory calculation. NO induced the conversion of paramagnetic Cu 2+ to diamagnetic Cu +, which blocked the photoinduced electron transfer process of NZ -Cu 2+, resulting in a remarkable enhancement of the emission spectra. The NZ -Cu 2+ probe possesses several advantages including high selectivity, low detection limit (12.9 nM), long emission wavelength (640 nm), large Stokes shift (201 nm), fast response time (60 s) and low cytotoxicity. More importantly, NZ -Cu 2+ has been successfully applied to detect NO in vivo by fluorescence imaging.